Involvement of parents in intervention for childhood speech sound disorders: a review of the evidence. Issue 6 (27th March 2016) - Sugden, Eleanor; Baker, Elise; Munro, Natalie; Williams, A. Lynn
Abstract: Background: Internationally, speech and language therapists (SLTs) are involving parents and providing home tasks in intervention for phonology‐based speech sound disorder (SSD). To ensure that SLTs' involvement of parents is guided by empirical research, a review of peer‐reviewed published evidence is needed. Aims: To provide SLTs and researchers with a comprehensive appraisal and analysis of peer‐reviewed published intervention research reporting parent involvement and the provision of home tasks in intervention studies for children with phonology‐based SSD. Methods & Procedures: A systematic search and review was conducted. Academic databases were searched for peer‐reviewed research papers published between 1979 and 2013 reporting on phonological intervention for SSD. Of the 176 papers that met the criteria, 61 were identified that reported on the involvement of parents and/or home tasks within the intervention. These papers were analysed using a quality appraisal tool. Details regarding the involvement of parents and home tasks were extracted and analysed to provide a summary of these practices within the evidence base. Main Contribution: Parents have been involved in intervention research for phonology‐based SSD. However, most of the peer‐reviewed published papers reporting this research have provided limited details regarding what this involved. This paucity of information presents challenges for SLTs wishing to integrate external evidence into their clinical services and clinical decision‐making. It also raises issues regarding treatment fidelity for researchers wishing to replicate published intervention research. Conclusions & Implications: The range of tasks in which parents were involved, and the limited details reported in the literature, present challenges for SLTs wanting to involve parents in intervention. Further high‐quality research reporting more detail regarding the involvement of parents and home tasks in intervention for SSD is needed.